Process Improvement Study in a Tire Factory - ARSLANKAYA, Seher; DEMİR, Asude (International Journal of Computational and Experimental Science and Engineering, 2023)
Today, motorsports is one of the sports branches with the world’s largest audience and fan base. The production techniques of the tires used in these organizations are an indispensable factor in order to be the pioneer of the sector. In this study, SWOT Analysis and Failure Modes and Effects Analysis were performed for two different production lines, and the superiority of the lines against each other was evaluated. The process to be improved on the excellent line was determined as a result of brainstorming by an expert team. After the changed parameters, the effects on the final product and the process were evaluated. The study was concluded by determining that all the changes made do not constitute an obstacle to the continuity of the process and the quality of the final product. Time analysis was made by video recording the process whose cycle time changed. As a result of the calculations made after the time analysis, the annual tire gain was calculated as 7299.